Attended and Unattended Automated Office Blood Pressure Measurements Have Better Agreement With Ambulatory Monitoring Than Conventional Office Readings - Emmanuel A. Andreadis; Charalampia V. Geladari; Epameinondas T. Angelopoulos; Florentia S. Savva; Anna I. Georgantoni; Vasilios Papademetriou (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
BackgroundAutomated office blood pressure (AOBP) measurement is superior to conventional office blood pressure (OBP) because it eliminates the “white coat effect” and shows a strong association with ambulatory blood pressure. Methods and ResultsWe conducted a cross‐sectional study in 146 participants with office hypertension, and we compared AOBP readings, taken with or without the presence of study personnel, before and after the conventional office readings to determine whether their variation in blood pressure showed a difference in blood pressure values. We also compared AOBP measurements with daytime ambulatory blood pressure monitoring and conventional office readings. The mean age of the studied population was 56±12 years, and 53.4% of participants were male. Bland–Altman analysis revealed a bias (ie, mean of the differences) of 0.6±6 mm Hg systolic for attended AOBP compared with unattended and 1.4±6 and 0.1±6 mm Hg bias for attended compared with unattended systolic AOBP when measurements were performed before and after conventional readings, respectively. A small bias was observed when unattended and attended systolic AOBP measurements were compared with daytime ambulatory blood pressure monitoring (1.3±13 and 0.6±13 mm Hg, respectively). Biases were higher for conventional OBP readings compared with unattended AOBP (−5.6±15 mm Hg for unattended AOBP and oscillometric OBP measured by a physician, −6.8±14 mm Hg for unattended AOBP and oscillometric OBP measured by a nurse, and −2.1±12 mm Hg for unattended AOBP and auscultatory OBP measured by a second physician). ConclusionsOur findings showed that independent of the presence or absence of medical staff, AOBP readings revealed similar values that were closer to daytime ambulatory blood pressure monitoring than conventional office readings, further supporting the use of AOBP in the clinical setting.